Allagelena monticola sp. n. (Araneae: Agelenidae), a new species of funnel-web spiders from northern Thailand - Chami-Kranon, Thanaphum; Likhitrakarn, Natdanai; Dankittipakul, Pakawin (Zootaxa, 2007)
A new species of the funnel-web spiders from Thailand, Allagelena monticola sp. n., is described and illustrated. The types of this species were collected from remnant patches of pristine evergreen hill forest in the Doi Inthanon National Park, Chiang Mai Province, northern Thailand. The new species resembles the widely distributed species A. opulenta (L. Koch), which is known from China, Korea and Japan. This discovery expands the known zoogeographical distribution of the genus Allagelena southwards into tropical Southeast Asia.